Understanding leadership in a world of shared problems: advancing network governance in large landscape conservation. Issue 3 (4th April 2016) - Imperial, Mark T; Ospina, Sonia; Johnston, Erik; O'Leary, Rosemary; Thomsen, Jennifer; Williams, Peter; Johnson, Shawn
Abstract : Conservation of large landscapes requires three interconnected types of leadership: collaborative leadership, in which network members share leadership functions at different points in time; distributive leadership, in which network processes provide local opportunities for members to act proactively for the benefit of the network; and architectural leadership, in which the structure of the network is intentionally designed to allow network processes to occur. In network governance, each leadership approach is necessary to achieve sustained, successful outcomes. We discuss each of these approaches to leadership and offer specific practices for leaders of networks, including: shaping the network's identity and vision, attracting members, instilling leadership skills in members, and advancing common interests. These practices are then illustrated in case studies.